1. −(a+b)−(c−d)−(e−f)=−a-b−c+d−e+f
2. (8ab+3b)−(6ab−3b)+4a=8ab+3b−6ab+3b+4a=2ab+6b+4а
если a=6 и b=3. 2*6*3+6*3+4*6=36+18+24=78
3. 0,2x²+0,04y² +0,16x²−0,07y²=0,36x²-0,03y²
(0,2x²+0,04y²) -(0,16x²−0,07y²)=0,2x²+0,04y²-0,16x²+0,07y=0.11у²+0.04х²
4. (9a−13b+29c)−(−24a+29b−24c) =9a−13b+29c+24a-29b+24c=33а-42b+53с
5. (637d−214d²)+(114d²−137d)= 637d−214d²+114d²−137d=500d-100d²
6. 16−(7h+5)+4= 16−7h-5+4=15−7h
7. (x²−4x+3)−(3x−2x²+4)=x²−4x+3−3x+2x²-4=3х²-7х-1; если x=2.
3х²-7х-1=3*2²-7*2-1=12-14-1=-3
8. x³+3x²−x+4x³+2x²−x +5x²−3x³+4x =2x³+10x²+2х
9. это 42, т.к. 42-24=18
3x - X < 6 - 8
2x < - 2
X < - 1
ответ ( - бесконечность ; - 1 )
2) 8 - 5( Х + 2 ) < 4( 1 - Х )
8 - 5х - 10 < 4 - 4х
- 2 - 5х < 4 - 4х
5х - 4х > - 2 - 4
Х > - 6
ответ ( - 6 ; + бесконечность )
3) - 6 < 5х - 1 < 5
- 6 + 1 < 5х < 5 + 1
- 5 < 5х < 6
- 1 < Х < 1,2
ответ ( - 1 ; 1,2 )